Integrasi Nilai-nilai Karakter dalam Pembelajaran Tematik SDN 1 Tamansari - Nabila Citra Kirana; Nadira Eka Syafira (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Instilling character values from an early age is a crucial foundation in shaping a generation that is morally upright, responsible, and capable of facing future challenges. This study aims to describe the forms, strategies, and effectiveness of integrating character values into thematic learning at SDN 1 Tamansari. The research employs a descriptive qualitative approach, with data collected through observations, in-depth interviews with classroom teachers, and documentation of learning instruments. The results indicate that character values such as religiosity, honesty, discipline, responsibility, social care, and cooperation are consistently integrated across various learning themes and subthemes. Teachers apply contextual approaches, group discussion methods, educational games, and reinforcement through role modeling to instill these values. In addition, a conducive learning environment and strong interpersonal relationships between teachers and students serve as key supporting factors in the successful integration of character education into the learning process. The challenges encountered include differences in students’ backgrounds and limited time to deliver thematic content comprehensively while incorporating character values. Nevertheless, observational findings show that the integration of character values has a positive impact on students’ attitudes and behaviors, both inside and outside the classroom. This study recommends the need for continuous teacher training and strong school policy support to strengthen character education in a systematic and sustainable manner.